Maximizing Economic Efficiency in Urban Mustard Farming through Pipe, Soil, and Bottle-Based Systems - Prawitasari, Putu Putri; Rafa Nafisah, Ghalda Syadza; Nurmalasari, Made Ratih; Ari Krismajayanti, Ni Putu; Megawati, Ida Ayu Putu (Lembaga Dongan Dosen, 2025)
Urban agriculture has gained recognition as an effective solution to urbanization's challenges, including food security and environmental sustainability. This study,